Perioperative Management for Full-Endoscopic Lumbar Discectomy: Consideration From the Perspective of Preventing Complication - Takeshi Hara; Yukoh Ohara (Neurospine, 2023)
In recent years, full-endoscopic discectomy (FED) has expanded its range of indications with the development of devices and various techniques. The advantage of FED over conventional surgery is that it is a minimally invasive procedure. However, intraoperative and postoperative precautions must be taken to prevent complications. It is necessary to avoid complications that could compromise the outcome of the procedure. Effective perioperative management is necessary to avoid complications; however, there is no set view for perioperative management in FED. In this study, we perform a literature review to examine the effectiveness of perioperative management methods for FED. The key to ensuring the efficacy and minimal invasiveness of FED is prevention of complications. Based on the result and literature review, we believe that the most manageable postoperative management after FED is prevention of recurrent disc herniation and hematoma formation. A drain should be placed to prevent postoperative hematoma formation. It is advisable to evaluate the patient’s symptoms and monitor C-reactive protein and erythrocyte sedimentation rate levels during the first week after surgery. Postoperative antibiotics were administered for 1 day.